Physiologic, metabolic, and nutritional attributes of collegiate synchronized swimmers - Costa, P. B.; Richmond, S. R.; Smith, C. R.; Currer, B.; Stecker, R. A.; Gieske, B. T.; Kemp, K.; Witherbee, K. E.; Kerksick, C. M. (International Journal of Sports Physiology and Performance, 2019)
Synchronized swimming is a sport that requires high levels of strength, power, and endurance, as well as artistic skill to perform in an aquatic environment. Purpose: The purpose of this study was to identify physiological characteristics and dietary habits of collegiate synchronized swimmers. Methods: A total of 21 female participants (mean [SD] age = 20.4 [1.6] y, height = 168.0 [4.9] cm, and weight = 64.4 [8.7] kg) performed resting metabolic rate test. Body composition was determined using skinfolds (4-site and 7-site) and dual-energy X-ray absorptiometry (DEXA). Dietary intake was assessed using 4-d dietary records. Results: Resting metabolic rate was 110.9 (10.5) kJ/kg normalized to body weight and calculated relative daily caloric intake was 121.4 (42.3) kJ/kg. Estimated energy availability ranged from 109.1 (52.1) to 126.7 (52.6) kJ/kg fat-free mass per day and was correlated (P = .045) to resting metabolic rate. Percentage body fat measured using DEXA (28.7% [4.8%] fat) was higher than both 4-site (25.7% [4.8%] fat, P = .001) and 7-site (25.3% [4.7%] fat, P = .001) skinfold values. No significant correlations were reported between bone mineral density, body composition, and dietary intake data. Conclusions: Synchronized swimmers have similar body composition and training habits as other competitive aquatic athletes. Dietary intake data revealed low energy availability and lower than recommended macronutrient levels.